Stimulating Research to Advance Evidence-Based Applications of Telehealth in Occupational Therapy. (July 2021) - Proffitt, Rachel; Cason, Jana; Little, Lauren; Pickett, Kristen A.
Occupational therapy focuses on therapeutic means to address participation in meaningful everyday tasks across the lifespan. No single setting is more conducive to this pursuit than individuals' authentic contexts. Occupational therapists are therefore uniquely suited to lead the charge toward stimulating research and advancing evidence-based application of telehealth. To this end, the American Occupational Therapy Foundation digitally convened their 2020 Planning Grant Collective to focus on the topic of Telehealth. Participants of the interdisciplinary collective collaboratively identified four themes: (1) Using technology to assess and intervene in the everyday context, (2) Partnerships with caregivers, (3) Telehealth delivery, and (4) Uniform data collection. Subgroups explored potential research and funding opportunities in their specialty area while also addressing the centralizing concepts of equity and diversity of telehealth delivery and COVID-19. Here, we provide a summary of the key concepts and recommendations from the 3 days of collaboration.